Employees' Organizational and Occupational Commitment in Equine Industry - Silvennoinen, Riitta (My University, 2004)
The objective of the study is to examine and analyze employees' organizational and occupational commitment in the equine industry. The study looks into employees’ primary commitment preferences, analyzes the factors affecting both commitment types as well as explores ways of building organizational commitment. The theoretical background of the study stems from the existing research on organizational and occupational commitment, which are also the key concepts used in the study. Organizational commitment refers to an employee’s belief in an organization’s goals and values, willingness to remain with their organization and to make an effort for the success of the organization. Occupational commitment, in turn, refers to an employee’s identification with and involvement in his/her profession. The research design is qualitative, comprising of a multiple case study and complementing interviews of other individuals working in the industry sector. The empirical data consists of 20 semi-structured interviews of company owners, riding instructors and horse care professionals: 9 in case companies and 11 complementary individual ones. The research results show that the equine sector employees demonstrate simultaneously organizational and occupational commitment, i.e. the commitment types are rather mutually complementary than exclusive. The existing research findings on antecedent variables of both commitment types seem to apply with minor modifications in the equine environment. The empirical evidence suggests that organizational commitment can be improved by strengthening the respective antecedent variables, especially job variables (role discretion, role clarity, business acumen) and organizational variables (work atmosphere, career development and work experiences) that both influence affective commitment.
Keywords: Organizational Commitment; Occupational Commitment; Equine Industry; Leisure Industry; Small Business; fi=Johtaminen ja organisaatiot|en=Management and Organization|